VD_FINDINFO Pron / 2012 / 95 vom 2. Mai 2012 - VD Tribunal cantonal (2012)
MESURE PROVISIONNELLE, DIVORCE, TRANSACTIONACCORD | 105 al. 1 CPC (CH), 117 CPC (CH), 122 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH), 65 al. 2 TFJC (2010), 67 al. 2 TFJC (2010)